QIRAAT AND IDENTITY CHALLENGES; STRENGTHENING ISLAMIC MODERATION THROUGH STUDYING VARIATIONS IN AL-QUR’AN READINGS - Lestari, Rosa (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
Qiraat, as a variation of the reading of the Qur'an, has an important role in strengthening Islamic moderation, as well as answering the challenges of the identity of Muslims in the contemporary world. This study aims to examine the contribution of qiraat, a variation of the reading of the Qur'an, in strengthening Islamic moderation and overcoming the challenges of the identity of Muslims in the contemporary world. The method used in this study is a qualitative approach with a literature study design, in which relevant literature is analyzed descriptively-analystically. Data were obtained from primary sources, such as the text of the Qur'an with various variations of the reading of qiraat, as well as tafsir works that discuss the influence of qiraat on religious understanding. The results of the study show that qiraat not only reflects diversity in the text of the Qur'an, but also becomes a symbol of tolerance and inclusiveness in Islam. In addition, this variation of reading plays an important role in building a moderate Islamic identity by respecting differences in interpretation, avoiding extremism, and strengthening the unity of the community. This study makes an important contribution to the development of contemporary Islamic thought, especially in encouraging acceptance of Muslim groups.